2006
DOI: 10.1111/j.1398-9995.2005.00913.x
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind, placebo‐controlled study of house dust mite immunotherapy in Chinese asthmatic patients

Abstract: One year treatment with Alutard SQ house dust mite immunotherapy significantly reduced symptoms and medication use in asthmatic subjects. This was associated with a greater subjective improvement in asthma control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
93
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 18 publications
13
93
0
1
Order By: Relevance
“…All these studies demonstrated that the AIT treated group had a significant decline in the medication score compared with the placebo group (54,55,134,234).…”
Section: Asthma Controlmentioning
confidence: 99%
See 4 more Smart Citations
“…All these studies demonstrated that the AIT treated group had a significant decline in the medication score compared with the placebo group (54,55,134,234).…”
Section: Asthma Controlmentioning
confidence: 99%
“…Patients with new sensitization have been shown to have higher atopy scores and medication scores for both rhinitis and asthma than patients without new sensitization, after 5 years of AIT treatment (50)(51)(52)55,56). Interestingly, one study has demonstrated that the risk of development of new sensitization was 3-fold higher in the control group than in the SIT-aq (SIT with aqueous extracts) group and 4-fold higher in the control group than in the SIT-ad (SIT with adsorbed extracts) group (57).…”
Section: The Risk Of Development Of New Sensitizationmentioning
confidence: 99%
See 3 more Smart Citations